The Natural History of Model Organisms: New opportunities at the wild frontier - Alfred, Jane; Baldwin, Ian T (eLife, 2015)
A better understanding of the natural history of model organisms will increase their value as model systems and also keep them at the forefront of research.
Keywords: the natural history of model organism; natural history; model organism